Effect of Fluid Dynamic Conditions on the Recovery of Abe Fermentation Products by Membrane-Based Dense Gas Extraction - Romero-Figueroa, J; Merlet-Venturelli, G; Cabezas-Cornejo, R; Plaza, A (Elsevier, 2015)
This work is focused on the application of membrane-based supercritical fluid extraction for the removal of fermentation products from an ABE (acetone/butanol/ethanol) mixture. The extraction process was implemented in a hollow fiber contactor where the liquid fed was circulated in the lumenside. Meanwhile, the extraction phase was dense carbon dioxide, circulated through the shell.A model solution, containing the three representative products of ABE fermentation broths was fed to the single PTFE fiber contactor with flow rates varying from 0.1 to 1.5mLmin-1. Dense CO2 with pressures between 7.0 and 9.0MPa at 40°C was circulated in countercurrent configuration.Experimental extraction percentages reached 70%, 50% and 27% for acetone, butanol and ethanol, respectively, in a single extraction step. When pressure was 9.0MPa and liquid feed flow rate was higher than 0.5mLmin-1, the extraction percentage of solutes and its transmembrane fluxes showed an unexpected decreasing, which was described by means of a phenomenological transfer model with variable membrane wettability. Thus, it has been demonstrated that the higher flow rates and pressure values can involve instability of the interface formed at the pore entrance and the liquid feed solution can penetrates into the membrane pores. © 2015 Elsevier B.V.
Keywords: Membrane-based extraction; Supercritical CO2; ABE fermentation products; Membrane wettability; Mass transfer